ECOTHEOLOGICAL MINDSET EDUCATION IN PERSPECTIVE YUSUF AL-QARADAWI - Sri Mulyani; Saiful Amien; Moh.Nurhakim (RADJA PUBLIKA, 2025)
The environment plays a very important role in human life. Humans as inhabitants of the environment on earth play an important role in preserving the environment. Yusuf al-Qardhawi emphasized that Islam pays great attention to the environment.Education must be able to change beliefs, values ​​and understanding about the importance of maintaining and preserving the environment to maintain quality and health. The research method in this article is carried out using the library research method. The collection technique used is a document where researchers collect books, journals, etc. according to the title. Furthermore, for the data analysis technique in this study, descriptive analysis, where data is analyzed in data description. The results of the study indicate that education is one way to form a mindset about the importance of maintaining the environment in accordance with Islamic values.